Employers ' Response to Workers With Progressive Cognitive Impairment: A Review of Policy in Canada. (17th December 2021) - McMurray, Josephine; Kokorelias, Kristina; Levy, AnneMarie; James, Krista; Reis, Logan; Boger, Jennifer; Astell, Arlene
Abstract: Longer lifespans, the gig economy, eligibility for government pensions, and more testing for age-related cognitive changes, increase the potential for workers developing mild cognitive impairment and/or early onset dementia (MCI|EOD) "on the job". This critical analysis assesses Canada's policy environment for employers when employees are diagnosed with MCI|EOD. Our search for policy literature included: a scoping review of academic literature involving Canadian-focused articles, and countries where novel or innovative policy had been evaluated and published; a search for Canadian court judgements and tribunal decisions; and a grey literature search in both Canadian and international sources, as innovation will often happen "at the margin" and updated policy may take years to be enacted and formalized. We used participatory research to obtain feedback from a broad group of stakeholders including employers, industry, professional organizations, and government, as well as people living with MCI/dementia, to ensure outputs were reflective of current policy. We found that: 1) Canadian federally-regulated employers are governed by similar Acts & Codes as the provinces and territories, with some notable exceptions, 2) Disability discrimination and accommodation case law in Canada is settled, however there are few cognitive impairment cases to provide specific guidance, 3) Scant empirical research in the scientific literature addresses policy that incents employers to build workspaces for employees with MCI|EOD that help them stay on the job longer. We conclude that engaging with employers to better understand their needs will help policy-makers to support them build workspaces that encourage productive engagement of all workers.